2009
DOI: 10.1080/19401490903046785
|View full text |Cite
|
Sign up to set email alerts
|

Thermal performance modelling of complex fenestration systems

Abstract: /npsi/ctrl?lang=en http://nparc.cisti-icist.nrc-cnrc.gc.ca/npsi/ctrl?lang=fr Access and use of this website and the material on it are subject to the Terms and Conditions set forth at http://nparc.cisti-icist.nrc-cnrc.gc.ca/npsi/jsp/nparc_cp.jsp?lang=en NRC Publications Archive Archives des publications du CNRCThis publication could be one of several versions: author's original, accepted manuscript or the publisher's version. / La version de cette publication peut être l'une des suivantes : la version prépubli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 19 publications
1
11
0
Order By: Relevance
“…Exterior mount blind configurations show good agreement between the proposed WINDOW model and previous studies by Shahid (2005), Naylor (2006), and Laouadi (2009). Agreement is also good with EN 13125 for fully-tilted high-emissivity slats.…”
Section: Comparison To Models From Literaturesupporting
confidence: 67%
See 2 more Smart Citations
“…Exterior mount blind configurations show good agreement between the proposed WINDOW model and previous studies by Shahid (2005), Naylor (2006), and Laouadi (2009). Agreement is also good with EN 13125 for fully-tilted high-emissivity slats.…”
Section: Comparison To Models From Literaturesupporting
confidence: 67%
“…Existing experimental work includes Clark et al (2013), Collins and Harrison (2004a), Cuevas et al (2010), Fang (2000), Garnet et al (1995), Naylor et al (2002a), and Naylor et al (2002b). Simulation and simplified model development is included in the work of Ye et al (1999), Laouadi (2009), Naylor and Shahid (2006), Marjanovic et al (2005), Oosthuizen et al (2005), Roelevelld et al (2010), Shahid and Naylor (2005), Collins (2004), and Wright (2008). Additional work involving SHGC of blinds under solar load has been done by Collins andHarrison (1999, 2004b), Harrison and van Wonderen (1998), Kotey et al (2009), andTait (2006).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The current model assumes constant temperatures in between the blind slats and window surface without any consideration of the mean air velocity. Another model based on the ISO 15099 standard has been developed by Laouadi (2009). His model expands on the ISO 15099 standard by using porous media equations to improve the convective and radiative heat transfer models of various layers inside the fenestration system.…”
Section: Introductionmentioning
confidence: 99%
“…Collins and Wright (1998) showed that early implementations of this model incorrectly accounted for IR transmission through layers, but this has since been corrected in the WINDOW software. Laouadi (2009) expanded on the van Dijk/ISO 15099 model by adding product type specific correlations for equivalent properties, flow between layers, and surface coefficients.…”
Section: Introductionmentioning
confidence: 99%